A structural intermediate pre-organizes the add adenine riboswitch for ligand recognition. Issue 10 (8th May 2021) - St-Pierre, Patrick; Shaw, Euan; Jacques, Samuel; Dalgarno, Paul A; Perez-Gonzalez, Cibran; Picard-Jean, Frédéric; Penedo, J Carlos; Lafontaine, Daniel A
Abstract: Riboswitches are RNA sequences that regulate gene expression by undergoing structural changes upon the specific binding of cellular metabolites. Crystal structures of purine-sensing riboswitches have revealed an intricate network of interactions surrounding the ligand in the bound complex. The mechanistic details about how the aptamer folding pathway is involved in the formation of the metabolite binding site have been previously shown to be highly important for the riboswitch regulatory activity. Here, a combination of single-molecule FRET and SHAPE assays have been used to characterize the folding pathway of the adenine riboswitch from Vibrio vulnificus . Experimental evidences suggest a folding process characterized by the presence of a structural intermediate involved in ligand recognition. This intermediate state acts as an open conformation to ensure ligand accessibility to the aptamer and folds into a structure nearly identical to the ligand-bound complex through a series of structural changes. This study demonstrates that the add riboswitch relies on the folding of a structural intermediate that pre-organizes the aptamer global structure and the ligand binding site to allow efficient metabolite sensing and riboswitch genetic regulation.